Analisis Implementasi dan Pelaporan Corporate Social Responsibility Perum Perumnas - Avriyani Siregar, Cut Vifde; Sukoharsono, Eko Ganis (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
It is inevitable that every activity of the company would have an impact on the environment, either positive nor negative impacts. Therefore, the company is obliged to take responsibility for the impact, especially for the company that makea negative impact on the environment around the company. At this time, the implementation of corporate social responsibility is not a new issue anymore. The existence of the impact had been demanding the company to take responsibility for it. Through the activities of the corporate social responsibility, companies are trying to balance the